Accelerating Li+ recovery kinetics of 5TiO2·2H2O adsorbents from original geothermal water by configuring TiO2·H2O phase - Lin Jing; Chunxi Hai; Xuemei Zuo; Lijuan Zhang; Shengde Dong; Yanxia Sun; Luxiang Ma; Qi Xu; Xin He; Yuan Zhou (Desalination, 2026)

Constructing structure-charge dual-regulated nanofiltration membranes via swelling embedding strategy for efficient separation - Ping Li; Yuan Zhou; Chunxi Hai; Wenjie Liu; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2026)

Three-dimensional conductive MX-NP/Chi@GF architecture with N, P dual-doping for membrane capacitive deionization desalination - Xueshuo Gao; Chang Tian; Haibo Li; Chunyi Sun; Beibei Liu; Yanxia Zhao; Wei Gao (Chemical Engineering Journal, 2026)

Distinct hydrolyzed Al-Ti species govern the coagulation behavior and subsequent anaerobic fermentation of CEPS sludge - Beibei Liu; Na Pan; Chunyi Sun; Weiying Xu; Wen Song; Liangguo Yan; Tao Yan; Yu Du; Yanxia Zhao; Baoyu Gao (Water Research, 2026)

Role of ultrasound-assisted KCl catalysis in characteristic flavor and quality of liquid smoke from cypress wood - Chun Liu; Gaoqi Tang; Xueliang Sun; Lingxia Sun; Yanxia Liu; Miaoyun Li; Gaiming Zhao; Lijun Zhao; Yaodo Zhu; Shudan Xiao; Wei Deng; Wentao Zhang (Food Chemistry, 2026)

Polydopamine nanocoating on biocontrol bacteria enables enhanced environmental resilience and agricultural performance - Yaqiang Wang; Xuewen Xie; Fasheng Shi; Yanxia Shi; Ali Chai; Lei Li; Sheng Xiang; Xianhua Sun; Baoju Li; Tengfei Fan (Chemical Engineering Journal, 2026)

BO33− lattice engineering regulates the flexibility of Li+ channels in LiFePO4 for Li+ extraction from Salt Lakes at low temperatures - Xin Zeng; Luxiang Ma; Jiacheng Li; Weiqing Lai; Huifang Li; Chaofei Song; Chunxi Hai; Shengde Dong; Yanxia Sun; Qi Xu; Xin He; Yuan Zhou (Chemical Engineering Journal, 2026)

Sustainable stabilization of loess via multi-solid waste-modified magnesium oxysulfate cement: Microstructure, mechanics, and environmental impact - Dongliang Chen; Qi Xu; Shengwen Tang; Jian Xiong; Luxiang Ma; Shengde Dong; Yanxia Sun; Xin He; Chunxi Hai; Yuan Zhou (Chemical Engineering Journal, 2026)

Anti-melanogenic bioactive peptides: Molecular mechanisms, source, preparation, structural optimization and cross-field prospective application - Qun Yu; Haozhe Li; Yanxia Sun; Yawei Yu (Trends in Food Science & Technology, 2026)

Genome-wide identification and expression analysis of the homeodomain-leucine zipper gene family in quinoa during the grain filling stage - Wenxuan Ge; Xueying Li; Xiuzhang Wang; Jiayu Liu; Yanxia Sun; Xiaoyong Wu (South African Journal of Botany, 2026)

Molecular mechanisms of dissolved organic matter transformation and microbial interactions in composting - Zishuai Zhang; Yanxia Hu; Guofeng Zu; Qiuling Dang; Xiaofan Sun; Yawen Wu (Bioresource Technology, 2026)

Particle size-dependent structure–activity relationship governing radical and electron-transfer pathways in peroxymonosulfate activation - Renjie Zhao; Xing Xu; Chunyi Sun; Xuguang Li; Beibei Liu; Wen Song; Tao Yan; Liangguo Yan; Yanxia Zhao (Water Research, 2026)

Transcription factor MdMYB6L represses anthocyanin biosynthesis of apple skin at low-altitude regions - Kai Wang; Xinrong Qin; Shuo Zhang; Yanxia Sun; Xueyong Zhang; Yan Tang; Daliang Liu; Xinxiang Xu; Xiaohong Liu; Xueqing Liu; Laiqing Song; Lingling Zhao (Plant Cell Reports, 2026)

Comparative study on pollution characteristics and ecological risk in Xiangshan Bay and its adjacent eastern sea area - Yanxia Wang; Honglei Jiang; Shengwei Xu; Xuelei Wang; Weiliang Shen; Lin Huang; Haihang Wang; Yuan Sun (Marine Pollution Bulletin, 2026)

Nonlinear maize yield responses to drought drive escalating regional vulnerabilities under climate change in China - Dan Wei; Yi Zhang; Yanxia Zhao; Qing Sun (Journal of Environmental Management, 2026)

Lithium recovery from clay lithium deposits using ammonium persulfate: Process and mechanism study - Zhixiang Li; Luxiang Ma; Weiqing Lai; Jiacheng Li; Chunxi Hai; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Yuan Zhou; Xiwei Qin; Yuliang Ma (Chemical Engineering Journal, 2026)

Preparation of high-load lithium-aluminum layered double hydroxide granules with excellent Li+ adsorption capacity and cycling stability from sulfate type brines - Qin Wang; Chunxi Hai; Junjie Huo; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu; Yuan Zhou (Water Research, 2026)

Swelling-thermal crosslinking engineered polyamide nanofiltration membranes for high-performance Mg2+/Li+ separation - Yu Tang; Shengde Dong; Ping Li; Ying Cheng; Wenjie Liu; Chuanjiang Cheng; Yanxia Sun; Qi Xu; Chunxi Hai; Yuan Zhou (Journal of Environmental Chemical Engineering, 2026)

From structural characteristics to metabolic characteristics: Structural morphological differences and proteomic analysis of Clostridium perfringens and its spores - Qingqing Ma; Yaodi Zhu; Qiancheng Tu; Miaoyun Li; Niancheng Hong; Shijie Liu; Lingxia Sun; Yanxia Liu; Lijun Zhao; Dong Liang (Food Research International, 2026)

Plant oil body engineering: A roadmap from multiscale structures to next-generation food systems - Wenwen Lv; Wenyi Zhao; Maoling Tan; Aili Wang; Yanan Cao; Yanxia Sun; Lianxin Peng (Food Chemistry, 2026)

6PPD-quinone promotes ovarian cancer progression: Insights from network toxicology, machine learning, and in vitro validation - Nannan Wang; Jingyu Zhu; Ningjuan Wu; Hang Yuan; Yanxia Sun; Xiaohe Dang; Shirui Wang; Yubei Li; Jie Chang; Xiaofeng Yang (Food and Chemical Toxicology, 2026)

Heat stress variation exerts a more pronounced effect than vapor pressure deficit on maize yield in Northeast China - Shuang Sun; Yanxia Zhao; Chunyi Wang; Yanling Song; Dasui Li; Nan Zhang; Qing Sun; Dingrong Wu; Yi Zhang (International Journal of Biometeorology, 2026)

Weather and Climate Services for Finance—The Development of Financial Meteorology in China - Yanxia Zhao; Qing Sun; Yi Zhang; Sining Chen; Li Liu; Muyuan Li; Yifang Ren (Advances in Atmospheric Sciences, 2026)

Reheating strategies for crispy pork: A comparative study of microwave and steaming treatments - Xueliang Sun; Gaoqi Tang; Zhidan Zheng; Changqing Wang; Shudan Xiao; Lingxia Sun; Lijun Zhao; Miaoyun Li; Yangyang Ma; Yanxia Liu (Food Research International, 2026)

Integrated morphological, transcriptomic, and metabolomic profiling reveals differential development mechanisms in two weeping forsythia genotypes during tissue culture - Yanxia He; Yanping Zheng; Jiaqi Geng; Yue Wang; Na Qi; Xu Lu; Xiaoxiao Wang; Yongjin Sun; Helong Wen; Xiaoya Liu; Xin Sun; Xianping Wang; et al. (Physiology and Molecular Biology of Plants, 2026)

Advances in understanding the Clostridial spore inner membrane - Jinyue Liu; Qingqing Ma; Yaodi Zhu; Miaoyun Li; Lijun Zhao; Dong Liang; Lingxia Sun; Yanxia Liu; Gaiming Zhao (Archives of Microbiology, 2026)

Multiscale hydrodynamic optimization and energy valorization in hydrogen-based membrane biofilm reactors: unraveling the lumen-shell interaction - Yanxia Xu; Peifeng Deng; Jinyi Tian; Ming Sun; Yuanyuan Qian; Liming Cui; Jinyang Zhang; Xuejing Yang (Journal of Water Process Engineering, 2026)

Ice-temperature storage suppresses starch retrogradation and enhances shelf life of slippery pork: mechanistic insights and kinetic Modeling - Sun Xueliang; Tang Gaoqi; Liu Yanxia; Li Miaoyun; Gai Zhengyan; Zhao Gaiming; Sun Lingxia; Xiao Shudan; Deng Wei; Wang Qi (Food Chemistry, 2026)

Tobacco–rapeseed system with moderate mineral fertiliser promotes yield by synergistically improving bacterial network complexity and soil fertility - Qi Miao; Lu Liu; Chen Wang; Hao Ying; Yingxin Guo; Dexun Wang; Yanxia Hu; Zhenling Cui; Junwei Sun; Junying Li; Jing Tian (European Journal of Agronomy, 2026)

Configuring 5TiO2·2H2O/C composite-type adsorbents for effectively recovering Li+ from original Salt Lake brines - Xuemei Zhuo; Chunxi Hai; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu; Masayoshi Fuji; Takashi Shirai; Yuan Zhou (Desalination, 2026)

The MADS-box transcription factor AaRLMA serves a crucial function in sustaining the integrity of cell wall, orchestrating secondary metabolites biosynthesis, and modulating pathogenicity in Alternaria alternata - Rong Li; Yiyang Liu; Xiwang Wang; Pengfei Sun; Meiqi Gao; Yanxia Zhang; Yang Bi; Yongcai Li (Postharvest Biology and Technology, 2026)

Effect of SO42− anions on lithium-aluminum layered double hydroxides: Implications for Li+ recovering from brines - Sijie Peng; Chunxi Hai; Junjie Huo; Qin Wang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu; Yuan Zhou (Chemical Engineering Journal, 2026)

Methyl jasmonate enhances isoflavone biosynthesis and antioxidant activities in Fusarium sulawense-infected soybean sprouts - Xiangyu Sun; Yining Cao; Yanxia Wang; Siqi Wu; Trust Beta; Xinchi Shi; Suyan Wang; Daniela D. Herrera-Balandrano; Pedro Laborda (Postharvest Biology and Technology, 2026)

Metabolomics and biochemical insights on the regulation of aging-related gut inflammation by sour meat peptides - Lijun Zhao; Qian Ding; Dezhen Meng; Shijie Liu; Yueyu Bai; Jong-Hoon Lee; Miaoyun Li; Dong Liang; Lingxia Sun; Yanxia Liu; Yaodi Zhu; Yangyang Ma (Food Bioscience, 2026)

Aluminum-modified diatomite efficiently catalyzes the CO2 desorption to achieve low-energy consumption regeneration of amine solution - Pan Li; Xin He; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Chunxi Hai; Wenyang Lu; Yuan Zhou (Journal of Environmental Chemical Engineering, 2025)

Investigation of the spoilage effects of interactions between dominant spoilage bacteria W. viridescens and P. agglomerans on marinated beef - Wenyan Ding; Miaoyun Li; Zhiyuan Sun; Yaodi Zhu; Lijun Zhao; Lingxia Sun; Huimin Niu; Fukang Dong; Yanxia Liu; Gaiming Zhao (Food Research International, 2025)

Trash to treasure: Cowhide was completely hydrolyzed by Bacillus velezensis LZ676 to prepare bioactive mixture and metabonomics analysis - Shijie Liu; Qian Ding; Yueyu Bai; Lijun Zhao; Miaoyun Li; Jong-Hoon Lee; Zihou Liu; Lingxia Sun; Yanxia Liu; Yangyang Ma; Gaiming Zhao; Dong Liang (Food Bioscience, 2025)

Construction of a rapid evaluation method for fermentation degree of low-fat fermented sour chicken meat based on Raman spectroscopy technology - Shijie Liu; Lijun Zhao; Yueyu Bai; Miaoyun Li; Jong-Hoon Lee; Yaodi Zhu; Qiancheng Tu; Huihui Zhi; Lingxia Sun; Yanxia Liu; Yangyang Ma; Gaiming Zhao; et al. (Food Control, 2025)

Hyperspectral modeling of colored dissolved organic matter (CDOM): Insights from machine learning and band ratio models - Jinyue Chen; Chongyang Wang; Shuisen Chen; Shilong Ren; Lei Fang; Yanxia Li; Wenjun Sun; Zhenyu Gao; Zehui Wang; Rao Fu; Guoqiang Wang; Qiao Wang (Estuarine, Coastal and Shelf Science, 2025)

Efficient lithium extraction from salt lakes brine via regulating the electric double-layer interface of high-loading film electrodes with CMC Li - Yawen Gao; Luxiang Ma; Xin Zeng; Zhixiang Li; Ting Li; Chunxi Hai; Tiandong Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Xiaowang Wu; et al. (Desalination, 2025)

Corrigendum to “Profitability analysis of renewable energy technologies for electrification and cooking in rural areas” [Bioresour. Technol. Rep. 30 (2025) 102122] - Ruben Zieba Falama; Yanxia Sun (Bioresource Technology Reports, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Cosolvent-modulated polyamide nanostructures enable precise Mg2+/Li+ separation for lithium recovery from brines - Ping Li; Yuan Zhou; Chunxi Hai; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2025)

Enhanced CO2 capture efficiency via catalytic Fe2O3-modified multi-walled carbon nanotubes in monoethanolamine - Lingling Li; Xin He; Pan Li; Xiaoqin Li; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Chunxi Hai; Maohong Fan; Yuan Zhou (Chemical Engineering Journal, 2025)

Bibliometric Analysis of Probiotic Bacillus in Food Science: Evolution of Research Trends and Systematic Evaluation - Lijun Zhao; Shijie Liu; Miaoyun Li; Jong-Hoon Lee; Yaodi Zhu; Dong Liang; Huihui Zhi; Qian Ding; Gaiming Zhao; Yangyang Ma; Lingxia Sun; Yanxia Liu (Probiotics and Antimicrobial Proteins, 2025)

FAM49B mediates tumor progression and poor prognosis of gastric cancer through activating PI3K/AKT pathway - Huimin Yang; Yanxia Ji; Yingzhe Ju; Yingying Shen; Xiaoyi Sun; Kaili Dai (Journal of Molecular Histology, 2025)

Sodium nitroprusside treatment affects energy metabolism and programmed cell death (PCD) of apple fruit during ripening - Yanxia Qiu; Jingyi Lv; Sijie Dong; Chenxu Sun; Yaxuan Wang; Yonghong Ge (Postharvest Biology and Technology, 2025)

PdSe2/WS2/PdSe2 unipolar barrier photodetector for visible-infrared polarization detection, synaptic plasticity simulation and neuromorphic visual system - Wenhao Fan; Hui Yan; Heng Li; Xinjian Liu; Yu Zhang; Weijie Bai; Mengyang Li; Yanxia Li; Jin Zhang; Jiayu Zhao; Shishuai Sun; Qingguo Wang; et al. (Chemical Engineering Journal, 2025)

Mowing enhances the contribution of glomalin over amino sugars to soil organic carbon pool following nitrogen cessation in temperate grasslands - Yanxia Ma; Huanhuan Cheng; Qiushi Ning; Tianran Sun (Plant and Soil, 2025)

E-pH diagram-guided low-temperature short-time sulfuric acid leaching for efficient recovery of lithium and iron from high-aluminum LiFePO4 black powder - Ke Xu; Shengde Dong; Chunxi Hai; Luxiang Ma; Yanxia Sun; Qi Xu; Xin He; Yuan Zhou (Waste Management, 2025)

Study on a functionalized ionic liquid [BIim][Cl3] for efficient dissolution of precious metals (Pd, Pt, Au, Rh) - Feng Feng; Heda Ding; Jiaying Zhang; Lu Yu; Yuxue Yue; Yanxia Sun; Lingling Guo; Xiaoliang Xu; Chunshan Lu; Qunfeng Zhang; Xiaonian Li (Hydrometallurgy, 2025)

Synthesis of green, highly stable, high-magnesium lithium-aluminum layered double hydroxide adsorbents for lithium extraction from brines - Junjie Huo; Chunxi Hai; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu; Yuan Zhou (Desalination, 2025)

Adolescent marginal zinc deficiency upregulated BDNF and TrkB expression, impaired hippocampal and cortical development, and induced abnormal behaviors in male mice - Rou Li; Qiwei Dai; Tian Yu; Yajing Sun; Yanxia Li; Tianyang Zhao; Hongbin Xu; Liang Wang; Yuxiang Wang; Xia Gao; Xiaozhi Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Dynamic adsorption and molecular simulation of aliphatic VOCs on industrial USY zeolites: Two-component competitive behavior - Wei Liu; Guiming Chen; Qing Li; Tengfei Guo; Yanxia Wang; Lingmin Sun; Jiangshan Zhao; Dongjun Lv; Xihao Yu; Min Wang; Weiwei Li; Zhigang Wang (Journal of Hazardous Materials, 2025)

Investigating the differences in β-Cyclodextrin derivatives / Hyperoside inclusion complexes: Dissolution properties, thermal stability, and antioxidant activity - Peiran Liu; Na Gan; Qinhong Li; Zhen Zeng; Jie Zhong; Xinhui Wang; Yanxia Sun; Di Wu (Food Chemistry, 2025)

In vivo imaging tool: High-brightness NIR-II “J-aggregates” based on TICT suppression strategy - Taihe Han; Shuai Mu; Qin Huang; Jiaxing Sun; Xin Lv; Yanxia Zhang; Xiaoyan Liu; Wei Guo; Haixia Zhang (Chemical Engineering Journal, 2025)

Humidity-actuated microphase separation to construct robust and tough amphibious polymer materials - Xiangrui Zhu; Yafei Sun; Jiajing Song; Kun Peng; Qingqing Luo; Qinglei Meng; Jianfeng Wang; Yanxia Cao; Wanjie Wang; Yanyu Yang (Chemical Engineering Journal, 2025)

Experimental research on the influence of wall effect on the structure of cumulated semi-cokes - Zhouzijing Yang; Peibin Zhang; Liying Zhang; Yuxiu Zhang; Xiangang Liu; Yuqiu Zhang; Haibo Gao; Yongqi Liu; Mingjun Sun; Yanxia Wang (Process Safety and Environmental Protection, 2025)

Enhancing hydrophilicity of thick electrodes via sulfonation reaction for lithium extraction from salt lake - Junyi Zhang; Luxiang Ma; Chunxi Hai; Tiandong Chen; Yawen Gao; You Xu; Wencheng Pan; Ju Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; et al. (Desalination, 2025)

Profitability analysis of renewable energy technologies for electrification and cooking in rural areas - Ruben Zieba Falama; Yanxia Sun (Bioresource Technology Reports, 2025)

Double difference accumulation SERS strategy for rapid separation and detection of probiotic Bacillus endospores and vegetative cells - Shijie Liu; Qian Ding; Yueyu Bai; Lijun Zhao; Miaoyun Li; Jong-Hoon Lee; Yaodi Zhu; Lingxia Sun; Yanxia Liu; Yangyang Ma; Gaiming Zhao; Dong Liang; et al. (Food Research International, 2025)

Factors affecting the efficiency of electrochemical lithium extraction: A systematic review from materials to processes technology - Junyi Zhang; Tiandong Chen; Luxiang Ma; Chunxi Hai; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Jitao Chen; Hongli Su; Yuan Zhou (Desalination, 2025)

Exergoeconomic analysis and machine learning-based optimization for a near-zero CO2 emission multi-generation system with freshwater production - Wenxing Liang; Yanxia Sun; Cong Han; Jinwen Yang; Fanhua Rong; Jitian Han (Desalination, 2025)

Accelerating the adsorption kinetics of layer-structured TiO2·H2O adsorbents for selectively separating Li+ from low-grade brines via Ce doping - Qiao Zhang; Chunxi Hai; Zhiqiang Zhu; Xuemei Zhuo; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu; Yuan Zhou (Chemical Engineering Journal, 2025)

Boosting the hydrogen storage performance of Mg-rich quaternary alloy hydrides via in-situ evolution of bidirectional catalytic phases - Ruijie Liu; Xinhao Jiang; Xinqiang Wang; Zhenglong Li; Xiaoying Yang; Jingbo Chen; Yanxia Liu; Wengang Cui; Fan Gao; Yong Gao; Fulai Qi; Chao Zheng; et al. (Chemical Engineering Journal, 2025)

Compression of Marine Environmental Data Using Convolutional Attention Autoencoder - Xuehai Sun; Peiyu Wang; Yanxia Zhou; Kedi Wu; Limin Huang; Xuewen Ma (Journal of Marine Science and Engineering, 2025)
Ocean temperature data is fundamental to the study of ocean dynamics and climate change, and its efficient compression and storage are critical for large-scale data analysis and transmission. However, traditional compression methods based on Fourier transform struggle to balance compression ratio and fidelity when confronted with the complex characteristics of marine environments. This study proposes a convolutional attention autoencoder (CAAE) to compress and reconstruct three-dimensional temperature fields and evaluates its performance across different depths and compression ratios. The experimental results indicate that although reconstruction error slightly increases with higher compression ratios, the proposed model achieves near-perfect compression and reconstruction of marine environmental data, performing robustly across various depths and spatial locations. This work offers a viable solution for the efficient and accurate compression of three-dimensional ocean data and provides valuable insights for the management of large-scale marine datasets.

Dynamic performance of TEPA-impregnated carbon nanofibers composites for direct air carbon capture in fixed bed columns - Si Chen; Xin He; Pan Li; Lingling Li; Meng Wang; Yulin Li; Qi Xu; Yanxia Sun; Chunxi Hai; Shengde Dong; Luxiang Ma; Yuan Zhou (Journal of Environmental Chemical Engineering, 2025)

Low-cost diatomite-loaded ZrO(OH)2 as an efficient green catalyst for amine-based carbon capture - Pan Li; Xingdong Qiu; Lingling Li; Si Chen; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Xin He; Yuan Zhou (Fuel, 2025)

Efficient carbon dioxide capture and reduced desorption energy consumption with bifunctional aluminium-modified MWCNTs catalyst - Lingling Li; Xin He; Pan Li; Si Chen; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Yuan Zhou (Fuel, 2025)

A self-powered PFC sensing platform via integrating aptamer-modified photoanode and Z-scheme signal amplifying photocathode for microcystin-LR detection - Ying Wang; Yuyi Wang; Lijun Wang; Rui Feng; Meng Sun; Yanxia Zhao; Tao Yan; Qin Wei (Analytica Chimica Acta, 2025)

The MYB-bHLH-NRAMP module modulates the cadmium sensitivity of quinoa by regulating cadmium transport and absorption - Wenjun Sun; Junyi Zhan; Liang Zou; Hui Chen; Xiaoyong Wu; Yanxia Sun; Gang Zhao; Yan Wan; Changying Liu; Qi Wu; Yusen Hou; Dabing Xiang (Journal of Hazardous Materials, 2025)

The composition, internal interactions, auxiliary preparation methods, and applications of type five resistant starch: A review - Tian Zhou; Qiang Wang; Zhiming Hu; Jingwei Huang; Xiaoqin Zheng; Yuanmou Tang; Dabing Xiang; Lianxin Peng; Yanxia Sun; Liang Zou; Chen Xia; Yan Wan (Food Hydrocolloids, 2025)

Development and evaluation of a sulfate precipitation method for separating key flocculated-species from titanium-based flocculant - Mingqian Hou; Wenhui Guo; Hao Xu; Chunyi Sun; Xu Zhao; Xiaomei Gao; Xuguang Li; Tao Yan; Shou-Qing Ni; Liangguo Yan; Yanxia Zhao (Water Research, 2025)

Investigating flavor and quality characteristics in Chinese bacon from different regions using integrated GC-IMS, electronic sensory assessment, and sensory analysis - Yanxia Liu; Chun Liu; Lingxia Sun; Miaoyun Li; Yaodi Zhu; Wei Deng; Jiahuan Yu; Wentao Zhang; Zhenning Song (Meat Science, 2025)

Pristine/magnesium-loaded biochar and ZVI affect rice grain arsenic speciation and cadmium accumulation through different pathways in an alkaline paddy soil - Chen Zhang; Dong Shi; Chao Wang; Guoxin Sun; Huafen Li; Yanxia Hu; Xiaona Li; Yanhui Hou; Ruilun Zheng (Journal of Environmental Sciences, 2025)

Corrigendum to “Frost risk assessment based on the frost-induced injury rate of tea buds: A case study of the Yuezhou Longjing tea production area, China” [Eur. J. Agron. 147 (2023) 126839] - Weiping Lou; Yanxia Zhao; Xueliu Huang; Tao Zhu; Ming Yang; Shengrong Deng; Zhuding Zhou; Yi Zhang; Qing Sun; Sining Chen (European Journal of Agronomy, 2025)

Rapid screening and identification strategy of lactic acid bacteria and yeasts based on Ramanomes technology and its application in fermented food - Shijie Liu; Lijun Zhao; Miaoyun Li; Jong-Hoon Lee; Yaodi Zhu; Yanxia Liu; Lingxia Sun; Yangyang Ma; Qiancheng Tu; Gaiming Zhao; Dong Liang (Food Research International, 2024)

Analysis of structural composition and antioxidant activity of traditional fermented sour meat peptides - Dezhen Meng; Lijun Zhao; Yaodi Zhu; Lingxia Sun; Miaoyun Li; Huilin Wu; Dong Liang; Yanxia Liu; Yangyang Ma; Gaiming Zhao; Shijie Liu (Food Chemistry, 2024)

Effects of Carnosine Addition in Low-Fishmeal Feed on the Growth Performance, Muscle Antioxidant Capacity and Flesh Quality of Orange-Spotted Grouper (Epinephelus coioides) - Dong Li; Weijun Chen; Yanxia Yin; Lulu Yang; Mingfan Chen; Yunzhang Sun; Jidan Ye (Fishes, 2024)
Carnosine is a natural dipeptide made up of L-histidine and β-alanine which is rich in muscle tissues and has multiple physiological functions. The current research aimed to investigate the effects of varied carnosine concentrations in low-fishmeal feed on the growth, muscle antioxidant capacity and flesh quality of orange-spotted grouper. Carnosine was supplemented at doses of 0, 10, 20, 40, 80, 160, and 320 mg/kg in low-fishmeal feed. Seven groups with three tanks of fish (11.4 ± 0.1 g/fish) were allotted one of the diets during the 8-week feeding trial. The growth rate, body protein content, muscle activities of superoxide dismutase and catalase, and muscle adhesiveness showed positive linear response and/or an open upward parabola with increasing carnosine concentrations, with a peak at 160 mg/kg of carnosine. Feed utilization, serum total protein content, gut trypsin activity, muscle glutathione peroxidase, total antioxidant capacity, muscle hardness, gumminess, chewiness and resilience followed the same pattern as the growth rate, reaching a peak at 320 mg/kg of carnosine; while the opposite trend was observed, reaching a minimum at 320 mg/kg for muscle malondialdehyde and 160 mg/kg for muscle liquid and water loss. The results indicated that appropriate carnosine addition could improve growth performance, muscle antioxidant capacity and flesh quality of grouper. The suitable inclusion concentration was estimated to be 195.14 mg/kg to achieve the best percent weight gain.

Investigation on the solidification effect and mechanism of loess utilizing magnesium oxysulfate cement as a curing agent - Xuerui Yan; Qi Xu; Miao Deng; Yanxia Sun; Xin He; Shengde Dong; Luxiang Ma; Chunxi Hai; Yuan Zhou (Science of The Total Environment, 2024)

Performance study of activated multi-walled carbon nanotubes on catalyzing amine-based carbon capture - Lingling Li; Xin He; Pan Li; Si Chen; Tongtong Wang; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Yuan Zhou (Fuel, 2024)

Configuring a structure self-curable lithium aluminum layered double hydroxide chloride type lithium adsorbents via a facile one-pot synergistical modification way - Junjie Huo; Chunxi Hai; Yanle Li; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu; Yuan Zhou (Chemical Engineering Journal, 2024)

Reduced actual vapor pressure exerts a significant influence on maize yield through vapor pressure deficit amid climate warming - Yi Zhang; Yanxia Zhao; Qing Sun; Sining Chen; Shao Sun; Li Liu (International Journal of Biometeorology, 2024)

Accelerating adsorption capacity and structural stability of Li1.6Mn1.6O4-type adsorbents via synergetic effect of in-situ configured Li2MnO3 layer - Panmin Yang; Chunxi Hai; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Luxiang Ma; Yuan Zhou (Chemical Engineering Journal, 2024)

Effects of quebracho–chestnut tannin extract supplementation on production performance, nitrogen partitioning, and rumen fermentation patterns in early-lactating Holstein cows - Meimei Wang; Yan Li; Shuai Ren; Yizhao Shen; Panliang Chen; Qiujia Cui; Yufeng Cao; Qiufeng Li; Hongjian Xu; Fengli Sun; Ning Ma; Yanxia Gao; et al. (Animal Feed Science and Technology, 2024)

Restored vegetation dominates the decrease in surface and subsurface runoff on the Loess Plateau - Xin Yan; João Pedro Nunes; Jineng Sun; Darrell W.S. Tang; Yanxia Wen; Zhi Li (Journal of Hydrology, 2024)

Performance activation mechanism of aluminum-based layered double hydroxides adsorbents for recovering Li+ by pH modulating - Yanle Li; Chunxi Hai; Junjie Huo; Wencheng Pan; Tiandong Chen; Xiang Li; Xin He; Yanxia Sun; Shengde Dong; Luxiang Ma; Qi Xu; Yuan Zhou (Chemical Engineering Journal, 2024)

Biochar-enhanced three-dimensional conductive network thick electrodes for efficient lithium extraction from salt lake brines with high Magnesia-lithium ratios - Junyi Zhang; Wencheng Pan; Yuan Zhou; Chunxi Hai; You Xu; Yan Zhao; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Jitao Chen; Hongli Su; et al. (Chemosphere, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

Constructing the 3D-conductive network-incorporated thick electrodes via melamine foam for lithium extraction - Junyi Zhang; Yuan Zhou; Chunxi Hai; Yawen Gao; Yan Zhao; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Jitao Chen; Hongli Su; Luxiang Ma (Desalination, 2024)

Shutters-Inspired metal ions coordination hydrogel Strain/Pressure sensor for joint behavior evaluation and flatfeet correction - Xiaoyu Guan; Yanxia Zhu; Bingyuan Zhang; Xuhui Sun; Mohammed A. Abosheasha; Chunwei Gong; Sai Zheng; Dongping Li; Qingxin Han; Meng An; Motoki Ueda; Yoshihiro Ito (Chemical Engineering Journal, 2024)

Nutrient runoff and leaching under various fertilizer treatments and pedogeographic conditions: A case study in tobacco (Nicotiana tabacum L.) fields of the Erhai Lake basin, China - Chen Wang; Qi Miao; Zhibiao Wei; Yingxin Guo; Junying Li; Zhiyong Fan; Yanxia Hu; Hong Zhang; Junwei Sun; Zhenling Cui (European Journal of Agronomy, 2024)

Widespread occurrence of two typical N, N’-substituted p-phenylenediamines and their quinones in humans: Association with oxidative stress and liver damage - Shiming Song; Yanxia Gao; Shuai Feng; Zhipeng Cheng; Haibao Huang; Jingchuan Xue; Tao Zhang; Hongwen Sun (Journal of Hazardous Materials, 2024)

Constructing of Fe-Cu bimetallic MOFs derived electro-Fenton cathode for efficient norfloxacin removal - Yixin Du; Zhenpeng Li; Rui Feng; Qing Liu; Yanming Yang; Meng Sun; Yanxia Zhao; Tao Yan; Liangguo Yan (Journal of Environmental Chemical Engineering, 2024)

Three-in-one: dispersant, emulsifier, and supporting electrolyte of hydrophobic ionic liquids for electrochemical collisions of single water droplets - Sijia Li; Yanxia Qiao; Hong Li; Yajie Zhang; Jingyan Zhang; Haiqiang Deng; Huiping Sun; Yan Li (Chemical Engineering Journal, 2024)

Global warming determines future increase in compound dry and hot days within wheat growing seasons worldwide - Yan He; Yanxia Zhao; Shao Sun; Jiayi Fang; Yi Zhang; Qing Sun; Li Liu; Yihong Duan; Xiaokang Hu; Peijun Shi (Climatic Change, 2024)
Compound dry and hot extremes are proved to be the most damaging climatic stressor to wheat thereby with grave implications for food security, thus it is critical to systematically reveal their changes under unabated global warming. In this study, we comprehensively investigate the global change in compound dry and hot days (CDHD) within dynamic wheat growing seasons during 2015–2100 under 4 socio-economic scenarios (SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5) based on the latest downscaled Coupled Model Intercomparison Project Phase 6 (CMIP6) models. Our results demonstrate a notable increase in CDHD’s frequency ( $${CDHD}_{f}$$ CDHD f ) and severity ( $${CDHD}_{s}$$ CDHD s ) worldwide under all SSPs, such increase is sharper over southern Asia in winter wheat growing season, and southern Canada, northern America, Ukraine, Turkey and northern Kazakhstan in spring wheat growing season. As the top 10 wheat producer, India and America will suffer much more detrimental CDHD in their wheat growing season. Adopting a low forcing pathway will mitigate CDHD risks in up to 93.3% of wheat areas. Positive dependence between droughts and heats in wheat growing season is found over more than 74.2% of wheat areas, which will effectively promote the frequency and severity of CDHD. Global warming will dominate the increase of CDHD directly by increasing hot days and indirectly by enhancing potential evapotranspiration thereby aggravating droughts. This study helps to optimize adaptation strategies for mitigating CDHD risks on wheat production, and provides new insights and analysis paradigm for investigating future variations in compound extremes occurring within dynamic crops growing seasons.

Quantitative identification of the co-exposure effects of e-waste pollutants on human oxidative stress by explainable machine learning - Luhan Yang; Tao Zhang; Yanxia Gao; Dairui Li; Rui Cui; Cheng Gu; Lei Wang; Hongwen Sun (Journal of Hazardous Materials, 2024)

Exploring the role of Maillard reaction and lipid oxidation in the advanced glycation end products of batter-coated meat products during frying - Yanxia Liu; Chun Liu; Xiaoshu Huang; Miaoyun Li; Gaiming Zhao; Lingxia Sun; Jiahuan Yu; Wei Deng (Food Research International, 2024)

Chiral gold nanorod vertical arrays for enantioselective chemiluminescence recognition of naproxen and mechanism revealing - Yanxia Song; Shengya Zhang; Dina Sun; Xinxin Li; Genping Meng; Xuan Zhang; Baodui Wang (Chemical Engineering Journal, 2024)

Relative role of soil nutrients vs. carbon availability on soil carbon mineralization in grassland receiving long-term N addition - Liangchao Jiang; Huanhuan Cheng; Yang Peng; Tianran Sun; Yingzhi Gao; Ruzhen Wang; Yanxia Ma; Junjie Yang; Qiang Yu; Haiyang Zhang; Xingguo Han; Qiushi Ning (Soil and Tillage Research, 2024)

The mechanisms of target and non-target resistance to QoIs in Corynespora Cassiicola - Bingxue Sun; Rongjia Zhou; Guangxue Zhu; Xuewen Xie; Ali Chai; Lei Li; Tengfei Fan; Shengping Zhang; Baoju Li; Yanxia Shi (Pesticide Biochemistry and Physiology, 2024)

Preparation of a novel healthy tiger nut oil-based margarine fat with low trans and saturated fatty acids - Shuaihao Dong; Yanxia Zhou; Shangde Sun; Xiaowei Chen (Food Chemistry, 2023)

Machine learning and particle swarm inspired success history based adaptive multi-objective differential evolution for optimization of heaving buoy point absorber - John Saveca; Yanxia Sun; Zenghui Wang (Ocean Engineering, 2023)

Within-person variability of urinary neonicotinoids and their metabolites and recommendation for sampling strategy - Yanxia Gao; Shaoyou Lu; Qing Zhao; Bo Zhang; Shiming Song; Mingwei Gui; Yu Wang; Hongwen Sun; Tao Zhang (Science of The Total Environment, 2023)

Dietary high β-conglycinin reduces the growth through enhancing hepatic lipid peroxidation and impairing intestinal barrier function of orange-spotted grouper (Epinephelus coioides) - Lulu Yang; Xingqiao Zhao; Yanxia Yin; Kun Wang; Yunzhang Sun; Jidan Ye (Frontiers in Marine Science, 2023)
β-conglycinin is one of the major soy antigen proteins in soybean meal (SBM) and exhibits growth inhibition and intestinal health damage in grouper, but the underlying mechanisms are still poorly understood. In this study, orange-spotted grouper ( Epinephelus coioides ) was used to investigate whether the poor growth performance induced by dietary β-conglycinin levels is associated with intestinal structural integrity disruption, the intestinal apoptosis and intestinal microbiota. The basal diet (FM diet) was formulated to contained 48% protein and 12% fat without SBM supplementation. Fish meal protein in the FM diet was replaced by SBM to prepare a high SBM diet (SBM diet). β-conglycinin at 3% and 7% were added into FM diets to prepare two diets (B-3 and B-7). Triplicate groups of fish (20 fish/tank) were fed one of the experimental diets twice daily in a feeding period of 8 weeks. Compared with FM diet, fish fed diets SBM and B-7 had decreased the growth rate, hepatosomatic index, whole-body lipid and ash contents, and increased whole-body moisture content. However, the maximum growth was observed for diet B-3 and was not different from that of FM diet. The liver total antioxidant capacity and glutathione peroxidase activity, the muscle layer thickness of middle and distal intestine, and the mucosal fold length of distal intestine were lower, while liver malondialdehyde content, intestinal diamine oxidase activity, d-lactic acid and endotoxin contents, and the number of intestinal apoptosis were higher in SBM and B-7 groups than that in FM and/or B-3 groups. SBM and B-7 diets down-regulated the intestinal expression of tight junction genes ( occludin , claudin-3 and ZO-1 ), apoptosis genes ( bcl-2 and bcl-xL ) and anti-inflammatory factor genes ( IκBα , TGF-β1 and IL-10 ), but up-regulated the intestinal expression of apoptosis genes ( caspase-3 , caspase-8 and caspase-9 ) and pro-inflammatory factor genes ( NF-κB1 , RelA , TAK1 , IKK , MyD88 , TNF-α , IL-1β , and IL-8 ) vs FM and/or B-3 diets. The richness and diversity indexes of OTUs, Chao1, ACE, Shannon and Simpson were not affected by dietary treatments. The relative abundances of intestinal bacteria (phylum Proteobacteria and genus Vibrio ) were generally higher, and relative abundance of phylum Tenericutes was lower in SBM and/or B-7 groups than that in B-3 group. The above results indicate that high dietary β-conglycinin level, rather than intermediate level could decrease liver antioxidant capacity, reshape the intestinal microbiota, and impair the intestinal normal morphology through disrupting the intestinal tight junction structure, increasing intestinal mucosal permeability, and promoting intestinal apoptosis, which in turn triggers intestinal inflammatory responses and the occurrence of enteritis, and ultimately leads to poor growth performance in fish.

Yeast enrichment facilitated lipid removal and bioconversion by black soldier fly larvae in the food waste treatment - Hongxu Lu; Yanxia Liu; Wenyue Shen; Yang Zhou; Xiangwei Ma; Shibo Sun; Xiaoying Dong; Fengyun Ji; Huiyan Tong; Jianqiang Xu; Gaohong He; Weiping Xu (Waste Management, 2023)

Frost risk assessment based on the frost-induced injury rate of tea buds: A case study of the Yuezhou Longjing tea production area, China - Weiping Lou; Yanxia Zhao; Xueliu Huang; Tao Zhu; Ming Yang; Shengrong Deng; Zhuding Zhou; Yi Zhang; Qing Sun; Sining Chen (European Journal of Agronomy, 2023)

Nocturnal influencing patterns on outdoor thermal environmental parameters along an urban road in summer: A perspective of visual index - Hongxuan Zhou; Yanxia Nie; Fenglin Zhou; Wenzhen Wang; Jing Sun (Urban Climate, 2023)

Peroxymonosulfate activation by Cu2O@CuO nanowires array-based electroactive filter for efficient ofloxacin removal - Rongshuai Wang; Haoqi Wang; Chongying Zhong; Qing Liu; Rui Feng; Yanxia Zhao; Meng Sun; Liangguo Yan; Tao Yan (Journal of Environmental Chemical Engineering, 2023)

Influence of urban surface compositions on outdoor thermal environmental parameters on an urban road: A combined two-aspect analysis - Hongxuan Zhou; Chen Xu; Hongtong Pu; Yanxia Nie; Jing Sun (Sustainable Cities and Society, 2023)

Natural edible pigments: A comprehensive review of resource, chemical classification, biosynthesis pathway, separated methods and application - Na Shen; Jiani Ren; Yanxia Liu; Wanqing Sun; Yuanrong Li; Huawei Xin; Yulei Cui (Food Chemistry, 2023)

Study on morphological traits, nutrient compositions and comparative metabolomics of diploid and tetraploid Tartary buckwheat sprouts during sprouting - Changying Liu; Xiaoqing You; Qingcheng Qiu; Xueling Ye; Qi Wu; Yan Wan; Liangzhen Jiang; Xiaoyong Wu; Yanxia Sun; Jingwei Huang; Yu Fan; Lianxin Peng; et al. (Food Research International, 2023)

Cyano-4′-Pentylbipheny dopant strategy for P3HT-Based CsPbI3 perovskite solar cells with a record efficiency and preeminent stability - Weihua Ren; Shiqi Li; Jingkun Ren; Yifan Liu; Yukun Wu; Qinjun Sun; Yanxia Cui; Yuying Hao (Chemical Engineering Journal, 2023)

Semi-unzipping of chitosan-sodium alginate polyelectrolyte gel for efficient capture of metallic mineral ions from tannery effluent - Xiaoyu Guan; Bingyuan Zhang; Dongping Li; Jiahe Ren; Yanxia Zhu; Zhe Sun; Yi Chen (Chemical Engineering Journal, 2023)

Transcriptome analysis reveals the mechanisms of hepatic injury caused by long-term environmental exposure to atrazine in juvenile common carp (Cyprinus carpio L.) - Jingbo Liu; Guangcheng Yang; Yanxia Gao; Xinran Li; Yuting Long; Shuling Wei; Yuxin Zhao; Shanshan Sun; Shujuan Gao (Environmental Science and Pollution Research, 2022)

Genome-wide association study of agronomic traits related to nitrogen use efficiency in wheat - Huawei Shi; Ming Chen; Lifeng Gao; Yanxia Wang; Yanming Bai; Huishu Yan; Chengjie Xu; Yongbin Zhou; Zhaoshi Xu; Jun Chen; Wensi Tang; Shuguang Wang; et al. (Theoretical and Applied Genetics, 2022)

Negative effects of heat stress on maize yield were compensated by increasing thermal time and declining cold stress in northeast China - Yi Zhang; Yanxia Zhao; Qing Sun; Sining Chen (International Journal of Biometeorology, 2022)

Site‐directed mutagenesis of the succinate dehydrogenase subunits B and D from Corynespora cassiicola reveals different fitness costs and sensitivities to succinate dehydrogenase inhibitors - Yanxia Shi; Bingxue Sun; Xuewen Xie; Ali Chai; Lei Li; Baoju Li (Environmental Microbiology, 2021)
Summary Carboxamide fungicides target succinate dehydrogenase (SDH). Recently published monitoring studies have shown that Corynespora cassiicola isolates are resistant to one or several SDH inhibitors (SDHIs) with amino acid substitutions in the SDH B and D subunits. We confirmed, by site‐directed mutagenesis of the sdhB and sdhD genes, that each of the mutations identified in the field strains of C. cassiicola conferred resistance to boscalid and, in some cases, cross‐resistance to other SDHIs (fluopyram, carboxin and penthiopyrad). Analyses of the enzyme activity and sdhB and sdhD gene expression show that modifications (SdhB_H278Y and SdhD_H105R) that result in a decline in SDH enzyme activity may be complemented by gene overexpression. The SdhB_H278Y, SdhB_I280V and SdhD_H105R mutants suffered large fitness penalties based on their biological properties, including conidia production and germination, mycelial growth, pathogenicity or survival abilities under environment stress. However, fitness cost was not found in the SdhB_H278R, SdhD_D95E and SdhD_G109V mutants. In the evaluation of resistance to boscalid in 2018 and 2019, the frequency of the SdhD_D95E and SdhD_G109V genotypes in the Liaoning and Shandong provinces changed dramatically compared with 2005–2017, from low resistance frequency (0.53% for D95E and 2.53% for G109V) to dominant resistance frequency (17.28% for D95E and 15.38% for G109V). Considering both the fitness and increased frequency of these genotypes, we may infer that the SdhD_D95E and SdhD_G109V mutants will be the dominant resistance mutants in field.

Procyanidins exhibits neuroprotective activities against cerebral ischemia reperfusion injury by inhibiting TLR4-NLRP3 inflammasome signal pathway - Bo Yang; Yanxia Sun; Chunchao Lv; Wei Zhang; Yizhao Chen (Psychopharmacology, 2020)

Improvement of the CERES-Rice model using controlled experiments and a Meta-analysis - Qing Sun; Yanxia Zhao; Yi Zhang; Xianghong Che; Zaiqiang Yang; Yanling Song; Xiaohui Zheng (Theoretical and Applied Climatology, 2020)

MicroRNA miR-7 and miR-17-92 in the Arcuate Nucleus of Mouse Hypothalamus Regulate Sex-Specific Diet-Induced Obesity - Yanxia Gao; Jiaheng Li; Zhen Zhang; Ruihan Zhang; Andrew Pollock; Tao Sun (Molecular Neurobiology, 2019)

Identification a novel clinical biomarker in early diagnosis of human non-small cell lung cancer - Yanxia Jin; Yajun Yang; Yanting Su; Xiangdong Ye; Wei Liu; Qing Yang; Jie Wang; Xiangning Fu; Yongsheng Gong; Hui Sun (Glycoconjugate Journal, 2019)

Titanium tetrachloride for silver nanoparticle-humic acid composite contaminant removal in coagulation-ultrafiltration hybrid process: floc property and membrane fouling - Yanxia Zhao; Yangyang Sun; Chang Tian; Baoyu Gao; Yan Wang; Hokyong Shon; Yanzhao Yang (Environmental Science and Pollution Research, 2017)

Arctic sea ice volume export through the Fram Strait from combined satellite and model data: 1979–2012 - Zehua Zhang; Haibo Bi; Ke Sun; Haijun Huang; Yanxia Liu; Liwen Yan (Acta Oceanologica Sinica, 2017)

Molecular regulation of hypothalamic development and physiological functions - Yanxia Gao; Tao Sun (Molecular Neurobiology, 2016)

A novel dual EGFR/HER2 inhibitor KU004 induces cell cycle arrest and apoptosis in HER2-overexpressing cancer cells - Chongchong Tian; Pingping Ding; Ziqiao Yuan; Han Li; Yanxia Zhao; Lan Sun; Qingming Guo; Zhenzhong Wang; Lixin Sun; Luyong Zhang; Zhenzhou Jiang (Apoptosis, 2015)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

Insufficient secretion of IL-10 by Tregs compromised its control on over-activated CD4+ T effector cells in newly diagnosed adult immune thrombocytopenia patients - Feng Li; Lili Ji; Weiguang Wang; Fanli Hua; Yanxia Zhan; Shanhua Zou; Ling Yuan; Yang Ke; Zhihui Min; Dongli Song; Lihua Sun; Hao Chen; et al. (Immunologic Research, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

Mammalian expression levels of cellulase and xylanase genes optimised by human codon usage are not necessarily higher than those optimised by the extremely biased approach - Zhiguo Liu; Yanxia Sun; Tao Feng; Qianqian Ji; Peiqing Cong; Yaosheng Chen; Zuyong He (Biotechnology Letters, 2014)

Chloroplast phylogeography of the East Asian Arcto‐Tertiary relict Tetracentron sinense (Trochodendraceae) - Yanxia Sun; Michael J. Moore; Liangliang Yue; Tao Feng; Haijia Chu; Shaotian Chen; Yunheng Ji; Hengchang Wang; Jianqiang Li (Journal of Biogeography, 2014)
Aim A phylogeographical study of the widespread but phylogenetically isolated East Asian endemic tree species Tetracentron sinense (Trochodendraceae) was performed to evaluate whether and how Pleistocene and pre‐Pleistocene climate changes helped to influence current phylogeographical patterns, and to describe the current patterns of genetic diversity and their implications for conservation. Location Southwestern and central subtropical China. Methods Sequences of four chloroplast spacer regions were obtained from 157 individuals of T. sinense . A haplotype network was constructed using tcs . Genetic diversity and differentiation, spatial analysis of molecular variance ( SAMOVA ) and analysis of molecular variance ( AMOVA ) were used to test for genetic structure. beast was used to estimate the divergence times between haplotypes. Historical demographic expansion was tested using pairwise mismatch distribution analysis. Results Of the 21 recovered haplotypes, three were widely distributed, but most were restricted to particular regions. Populations with high haplotype diversity were located in western Hubei, southern Sichuan and southern Chongqing. The two earliest‐diverging haplotypes were found in southwestern China. The haplotype distribution of T. sinense demonstrated significant phylogeographical structure ( N ST > G ST ; P 0.05). The best partitioning of genetic diversity by SAMOVA ( K = 5) produced groups that matched the main tcs ‐derived clades. Two independent range expansions within SAMOVA ‐derived groups 2 and 3 were dated to approximately 399 and 311 ka, respectively. The time to the most recent common ancestor of all haplotypes was 9.6 (95% highest posterior density: 27.0–2.2) Ma, but most of the haplotype diversity appeared during the Quaternary. Main conclusions The extant distribution of T. sinense is likely to have been shaped by both pre‐Quaternary and Pleistocene climate changes. Southwestern China may have served as an important refugium for T. sinense throughout the Neogene, while the species also occupied multiple refugia during the late Pleistocene glacial periods. Populations of T. sinense were resolved into five allopatric groups, between which there is apparently no seed movement.

Berberine inhibits the growth of human colorectal adenocarcinoma in vitro and in vivo - Yuchen Cai; Qing Xia; Rongzhen Luo; Peiyu Huang; Yueli Sun; Yanxia Shi; Wenqi Jiang (Journal of Natural Medicines, 2014)

Lentiviral Vector-Mediated siRNA Knockdown of c-MYC: Cell Growth Inhibition and Cell Cycle Arrest at G2/M Phase in Jijoye Cells - Aiqin Song; Junli Ye; Kunpeng Zhang; Lirong Sun; Yanxia Zhao; Hongsheng Yu (Biochemical Genetics, 2013)

Optimization on Antimicrobial Effects of Natural Compound Preservative Against B. cereus and E. coli by RSM - Xianqing Huang; Miaoyun Li; Gaiming Zhao; Xiaoping Gao; Qiuhui Zhang; Lingxia Sun; Yanxia Liu; Wenshui Xia (International Journal of Peptide Research and Therapeutics, 2012)

A novel mouse CD133 binding-peptide screened by phage display inhibits cancer cell motility in vitro - Jinmin Sun; Chao Zhang; Guobing Liu; Hong Liu; Chunping Zhou; Yanxia Lu; Chang Zhou; Li Yuan; Xuenong Li (Clinical & Experimental Metastasis, 2012)